EGFR tyrosine kinase targeted compounds - Gabr, Moustafa T.; El-Gohary, Nadia S.; El-Bendary, Eman R.; El-Kerdawy, Mohamed M. (Technische Universität Dortmund, 2014)
In this study, we illustrate computer aided drug design of new benzothiazole and pyrimido[2,1-b]benzothiazole derivatives as epidermal growth factor receptor tyrosine kinase (EGFR-TK) inhibitors. Compounds 1-5 were screened at NCI, USA, for antitumor activity against non-small cell lung cancer (NCI-H522), colon cancer (HCT-116, HCT-15 and HT29) and breast cancer (MDA-MB-468 and MDA-MB-231/ATCC) cell lines in which EGFR is overexpressed in varying levels. Results indicated that these compounds are more potent antitumor agents compared to erlotinib against HT29 and MDA-MB-231/ATCC cell lines. Compound 3 showed GI50 value of 22.3 nM against NCI-H522 cell line, while erlotinib exhibited GI50 value of 1 μM against the same cell line. In addition, these compounds were studied for their EGFR tyrosine kinase inhibitory activity. Virtual screening utilizing molecular modeling and QSAR techniques enabled the understanding of the pharmacophoric requirements for antitumor activity. Docking the designed compounds into the ATP binding site of EGFR-TK domain was done to predict the analogous binding mode of these compounds to the EGFR-TK inhibitors.
in vitro antitumor activity and molecular modeling studies of new benzothiazole and pyrimido[2,1-b]benzothiazole derivatives
EXCLI Journal ; Vol. 13, 2014
Keywords: enzothiazoles; pyrimidobenzothiazoles; antitumor activity; EGFR tyrosine kinase inhibitory activity; molecular modeling; 610